EFFECT OF FINANCIAL LITERACY AND FINANCIAL BEHAVIOR OF FINANCIAL SATISFACTION AT PROFESSIONAL BASKETBALL ATHLETES INDONESIA - Margerita Wenny Jessica; Njo Anastasia; Dewi Pertiwi (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
This study aims to determine the effect of financial literacy and financial Behavior on Indonesian professional basketball athletes. The population in this study is Indonesian professional basketball athletes who are the members of the Indonesian Basketball League (IBL) 2021. The sample in this study is Indonesian professional basketball athletes who have credit cards and investments. Sources of data in this study through the distribution of questionnaires. The data analysis method uses analysis Partial Least Square (PLS). This analysis shows that financial literacy and financial behavior have a significant effect on financial satisfaction.